Shear behaviour and design of cold-formed steel box girders with tubular flanges and sinusoidal corrugated webs. (May 2022) - Wu, Yangwei; Du, Xinxi; Yuan, Huanxin; Zhou, Man
Abstract: The shear behaviour of cold-formed steel box girders assembled from tubular flanges and sinusoidal corrugated webs was experimentally and numerically investigated in this paper. A total of twelve cold-formed steel box girder specimens were fabricated by self-drilling screws, wherein sinusoidal corrugated webs with two different corrugations were adopted. The fabricated box girder specimens were tested to failure subjected to three-point bending, and the shear performance and the corresponding failure modes were examined. Before testing, the material properties of the employed cold-formed steel grades were acquired by tensile coupon tests, and the mechanical properties of the adopted single-screw connections and double-screw connections were extracted from single lap shear tests. The obtained experimental results of tested box girder specimens were further used to validate finite element (FE) models developed by ABAQUS. Upon validation of the developed FE models, the influences of the height of tubular flanges, the web aspect ratio and the corrugation ratio were evaluated. Based on the obtained experimental and numerical results, a simplified design method for predicting the shear strength of cold-formed steel box girders with tubular flanges and sinusoidal corrugated webs was proposed.